Análisis descriptivo del índice de inteligencia emocional percibida y su relación con el rendimiento académico en estudiantes universitarios (2019)
This research project aims to describe the relationship between perceived Emotional Intelligence and Academic Performance in third semester students of the Civil Engineering program of the Universidad de la Costa Corporation. Due to the characteristics of the research, it was oriented to a mixed approach and with a descriptive scope, directed under a non-experimental transactional design. The sampling was of probabilistic type with a representative sample of 122 students. To measure the index of perceived Emotional Intelligence, the TMMS-24 test of Adaptación de Fernández-Berrocal, P., Extremera, N. y Ramos, N. (2004) was used as an instrument; and for Academic Performance, the final semester average of the sample was taken into account. In order to evaluate the relationship between the variables, the statistical program SPSS was used, where it was obtained as a result that the dimensions of greater relationship with low academic performance are high emotional clarity with an inverse relationship and low emotional repair with a proportional relationship. Finally, it was concluded that when describing the relationship between emotional intelligence and academic performance, it was found that there is a relationship between these variables.